Gender price gaps in Central Kenyan vegetable wet markets - Lutz Depenbusch (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2017)
Using survey data from Central Kenya, I find that the difference in prices received by female compared to male vegetable traders changes significantly in men's favor when the size of the transaction increases, ceteris paribus. This pattern in the price gap drives a gender difference in the value added by traders. If women had the same characteristics as men, they would make a 26.82 percent higher mark-up than men in the lowest quartile by traded quantities and receive the same price as men in the top quartile. Amongst suppliers, the price difference between men and women is significantly more favorable for women in rural compared to urban areas, when controlling for differences in other characteristics. Due to this effect, women experience a much smaller price reduction than men when selling in rural instead of urban areas. However, differences in the observable characteristics prevent female traders and suppliers from utilizing the advantage they have in part of the market. The results highlight the barriers in integrating women in large-scale vegetable trade, despite their traditional role in local vegetable trade. Furthermore, I show that gender values of the traders can explain the price gap among rural suppliers. This supports earlier findings connecting the gender price gap with gender stereotypes.
Keywords: D63; J16; O13; Q13; 330; gender; Gender Price Gap; inequality; value chains; food industry transformation; East Africa